Very short-lived halocarbons in the Malaysian atmosphere and their possible sources / Mohd Shahrul Mohd Nadzir - Mohd Shahrul, Mohd Nadzir (2012)

(untitled)
This doctoral thesis investigates biogenic emissions of selected Very Short-lived Species (VSLS) bromocarbons like bromoform (CHBr3), dibromomethane (CH2Br2), dibromochloromethane (CHBr2Cl) and selected chlorocarbons like chloroform (CHCl3) and tetrechloroethylene (C2Cl4) from different environments through ground and a shipborne field campaign. Brominated halocarbon is an atmospheric trace gas and a major source of atmospheric bromine. Recent estimates of brominated halocarbon sources and sinks indicate anthropogenic sources to be negligible. The major source of atmospheric brominated compounds is believed to be from marine especially coastal area. The production pathways of brominated compounds in the ocean are, however, poorly understood. Measurements were made using a μ-Dirac, which is a self-built instrument, consisting of a continuously operating gas chromatograph (GC), equipped with electron capture detector (ECD). This system was used for 3 ground field long term measurement in the coastal and tropical area to measure the air concentrations and the atmospheric dry gas mole fractions of the selected VSLS bromocarbons. The correlations plot of the mixing ratios between well correlated bromocarbons VSLS suggests that the bromocarbons species were emitted from biogenic or anthropogenic sources for both long term and short term measurement. Laboratory experiments were also conducted to test the hypothesis that bromocarbons produced in the ocean’s surface water are by marine plant like seaweeds, instead of direct biological production by phytoplankton or bacteria. The experiments were conducted on 7 types of seaweeds differentiated by its groups red, brown and green. A commercial purge and trap connected to a commercial GC-ECD was used to measure the VSLS halocarbons in seawater. The lab production studies showed diurnal cycle in the iii water samples. The concentration increased with increasing light intensity and sea surface temperature (SST) showing the highest concentration level at mid-day. The production of bromocarbons VSLS observed in all experiments kept in the sunlight was five times higher than the production from incubations kept in the dark. This strongly indicates photochemical production with no direct influence by biota. The mean photochemical production rate of the bromocarbons VSLS from each experiment was 1 to 137 pmol per g-1 FW-1 h-1, where, the red seaweeds was the highest producer followed by brown and green. The bromoperoxidase (BPO) enzyme was also extracted from all types of seaweeds, and result shows high BPO activity in red followed with brown and green seaweeds. From these results, it can be concluded that the photochemical production of bromocarbons VSLS plays an important role that may be dominant, in contributing to the tropospheric and stratospheric ozone depletion over the tropical region.